Moving north: Warmer waters expand populations of deep-water cartilaginous fishes into Arctic waters - Romaric Jac; Jon Albretsen; Hannes Höffle; Robert J. Lennox; Arved Staby; Fabian Zimmermann; Claudia Junge (PLoS ONE, 2026)
Continental shelf and deep ocean ecosystems are increasingly exposed to anthropogenic pressures including commercial fishing and climate change related environmental stressors. Among the most vulnerable taxa are chondrichthyans due to their life histories with low reproductive output and therefore lower rebound potentials. In temperate regions, many chondrichthyan species are expected to undergo poleward distributional shifts in response to ocean warming. However, the extent and drivers of these shifts remain poorly understood, particularly in deep-water environments. This study aims to assess long-term trends in distribution and abundance for three cartilaginous fish species in the Northeast Atlantic Ocean: the rabbitfish ( Chimaera monstrosa ), the velvet-belly lanternshark ( Etmopterus spinax ), and the blackmouth catshark ( Galeus melastomus ). Focusing on the northern fringe of their distribution, 26 years (1995–2020) of standardised data from Norwegian scientific bottom trawl surveys were analysed using generalized additive models and GIS-based spatial mapping. The results indicate that all three species have undergone significant northward shifts in abundance over the past two decades, although the magnitude and rate varied among species. Several of their prey species exhibited similar latitudinal shifts, suggesting a potential trophic linkage in response to changing thermal regimes. These findings support the hypothesis that warming waters in northern latitudes are driving the poleward redistribution of deep-water chondrichthyans as they seek to remain within their thermal preference ranges. Understanding these spatial responses is critical for informing conservation strategies and future fisheries management in rapidly changing high-latitude marine ecosystems.